A study on the records retention and disposition practices of the Commission on Higher Education - Manahan, Mary Joy B. (2009)
The Commission on Higher Education (CHED) is an important government agency that carries out different functions and responsibilities in the higher education sector of the country. It consequently accumulates voluminous records which are created, received, maintained and used in its numerous transactions. These records serve as the essential building blocks for the Commission's effective service delivery. This study examined the record-keeping practices of the /commission, specifically its records retention and disposition practices. Good record-keeping practices affects the Commission's level of efficiency and efficacy (or inefficiency/inefficacy) in the performance of its duties and responsibilities.